DIPEPTIDYL PEPTIDASE-4 (DPP-4) INHIBITION: A NOVEL APPROACH FOR THE TREATMENT OF TYPE II DIABETES MELLITUS - NISHAD GABHE; RUPALI TASGOANKAR; BHARAT DAGADE; DEEPESH RAO; PRADNYA SAWANT; ADITEE SHIRODKAR (International Journal of Pharma and Bio Sciences, 2013)
Diabetes Mellitus is a metabolic disorder characterized by hyperglycemia. The prevalence of Diabetes is on the rise, more alarmingly in the developing nations. It is projected that as many as 40-45% of persons aged 65 or older have either Type II Diabetes or its precursor state, Impaired Glucose Tolerance (IGT). The current therapeutic strategies for Type II Diabetes are relatively limited, and involve insulin therapy for Type I Diabetes and Oral Hypoglycemic Agents (OHAs) such as Sulfonylureas, Metformin and the Thiazolidinediones as the primary line of treatment for Type II Diabetes. Combination therapy with one or more of these agents is also a viable option. A wide variety of therapeutic approaches are now being examined for Type II Diabetes. Dipeptidyl peptidase IV (DPP IV), a key regulator of incretinhormones, glucagon-like peptide (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP), remains an attractive target in diabetes as it enhances glucose (nutrient) dependent insulin secretion. The present review will give an insight into the development of several DPP-4 inhibitors and their potential prospects in the treatment of Type II Diabetes Mellitus.